Evaluation of 2013 Curriculum Implementation In Economic Learning Class Xi In Madrasah Aliyah Dakwah Islamiyah Putra Nurul Hakim Kediri West Lombok - Lalu Hendra Wijaya; Maimun Sholeh (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
Abstract: This study aims to find out how to plan the implementation of the 2013 curriculum, the approach used in the 2013 curriculum, the form of assessment in the 2013 curriculum and the constraints faced in implementing learning in class XI Economics in Madrasah Aliyah Dakwah Islamiyah Putra Nurul Hakim Kediri West Lombok . This research includes qualitative research, Evaluation Model with the Goal Oriented Evaluation Model approach. Collecting data in research using observation instruments, interviews, and documentation. Based on the results of research on the implementation of the 2013 curriculum in IPS subjects, it shows that the implementation of the curriculum has not been carried out well, caused by several things namely, starting from training on the 2013 curriculum that schools have not yet held, the teacher's understanding of the RPP curriculum that is lacking, for teachers and students, do not have an Economics handbook on the 2013 curriculum. Researchers offer solutions to improve learning outcomes in education, all teachers must be empowered and demanded to understand the substance of the curriculum and its application in the learning process and by using various learning methods and making student worksheets that are in accordance with learning materials that relate to the environment of students as support for the implementation of the 2013 Curriculum implementation. Abstrak: Penelitian ini bertujuan untuk mengetahui bagaimana perencanaan implementasi kurikulum 2013, pendekatan yang digunakan pada kurikulum 2013, bentuk asesmen pada kurikulum 2013 dan kendala yang dihadapi dalam pelaksanaan pembelajaran pada siswa kelas XI Ekonomi di Madrasah Aliyah Dakwah Islamiyah Putra Nurul Hakim Kediri Lombok Barat. Penelitian ini termasuk penelitian kualitatif Model Evaluasi dengan pendekatan Model Evaluasi Berorientasi Tujuan. Pengumpulan data dalam penelitian menggunakan instrumen observasi, wawancara, dan dokumentasi. Berdasarkan hasil penelitian terhadap implementasi kurikulum 2013 pada mata pelajaran IPS menunjukkan bahwa implementasi kurikulum belum terlaksana dengan baik yang disebabkan oleh beberapa hal yaitu mulai dari pelatihan kurikulum 2013 yang belum dilakukan sekolah. diadakan, pemahaman guru tentang kurikulum RPP yang kurang, bagi guru dan siswa, belum memiliki buku pedoman Ilmu Ekonomi pada kurikulum 2013. Peneliti menawarkan solusi untuk meningkatkan hasil pembelajaran dalam pendidikan, semua guru harus di berdayakan dan dituntut harus paham tentang substansi kurikulum dan penerapannya dalam proses pembelajaran serta dengan menggunakan berbagai metode pembelajaran dan membuat lembar kerja siswa yang sesuai dengan materi pembelajaran yang mengkaitkannya dengan lingkungan peserta didik sebagai pendukung untuk terlaksananya penerapan Kurikulum 2013